Offshoring versus backshoring: Empirically derived bundles of relocation drivers, and their relationship with benefits. Issue 3 (June 2019) - Johansson, Malin; Olhager, Jan; Heikkilä, Jussi; Stentoft, Jan
Abstract: This paper describes an empirically derived classification of the various factors that influence offshoring and backshoring decisions based on data from 275 offshoring and 160 backshoring projects. The study developed one set of factor bundles for offshoring and another set of such bundles for backshoring; these sets were then compared, and their relationships with post-relocation benefits were analyzed. These benefits were also grouped into bundles based on the empirical relationships. This research contributes an empirically derived classification scheme of decision factors for both offshoring and backshoring as well as an analysis of the relationships between decision factors and benefits for each type of relocation direction. Highlights: Empirically derived classification of offshoring and backshoring drivers. Data from 275 offshoring and 160 backshoring projects. Comparing the driver bundles for offshoring and backshoring. Empirical analysis of the relationship between driver bundles and performance. Comparing these relationships for offshoring and backshoring.